Correlation between Individual Characteristics and Work Position with Work Fatigue on Workers - Irsyad Yudisianto; Abdul Rohim Tualeka; Noeroel Widajati (The Indonesian Journal of Occupational Safety and Health, 2021)
Introduction: Work fatigue is a condition of decreased efficiency and resilience of workers, which can interfere the companys’ productivity. Job fatigue can be caused by the performance, duration, and effort (work position) of the workers. Based on the observations, workers at the expedition sub units of PT X needed to lift 200 to 400kg heavy loads. The activity of lifting very heavy weights can cause fatigue. One form of physical fatigue indicators is an increase in lactic acid in the blood. The purpose of this study was to analyze the correlation between workers’ characteristics and work position with work fatigue among workers in the expedition sub units of PT X. Methods: This research was a quantitative study with a cross sectional design. The population of this study was 36 people. This research used total sampling. The independent variable were individual characteristics and work position as measured using REBA tools, and the dependent variable was work fatigue as measured using lactic acid levels in blood. Data was analyzed using statistical tools to obtain the value of correlation coefficient between variables. Result: The results showed that there was a weak positive correlation between workers’ characteristics and physical fatigue. The results showed that the coefficient value between work position and physical fatigue was 0.354. The coefficient figure indicated a weak positive correlation between work position and work fatigue. Conclusion: There was a correlation between work position and work fatigue in workers.Keywords: ergonomics, lactic acid, REBA, work fatigue, work position